Implementasi SERVQUAL dalam perspektif Islam: kualitas pelayanan terhadap kepuasan masyarakat pada pelayanan konsumen unit usaha syariah di Pondok Pesantren Riyadlul Jannah Pacet Mojokerto - Didi Sudira (FADZAT: Jurnal Ekonomi Syariah, 2020)
The level of customer satisfaction with service is an important factor in developing a service delivery system that is responsive to consumer needs, minimizes costs and time and maximizes the impact of services on the target population. The objectives of this study are: 1) To analyze the quality of service which consists of speed, friendliness, knowledge, number of services and appearance of formality, which have a simultaneous effect on community satisfaction with customer service. 2) Analyzing the quality of service which consists of speed, friendliness, knowledge, number of services and appearance of formality has a partial effect on community satisfaction with customer service. 3) Analyze among the quality of service which consists of speed, friendliness, knowledge, number of services and appearance of formality which have a dominant effect on community satisfaction in customer service. This research is an explanatory research. The population in this study was 15580 households. The method of sampling in this research is this research uses a simple random sampling system, from the members of the population taken as a sample is as many as 99 respondents. In this study the authors used multiple linear regression analysis techniques. technique, it is explained briefly between variables. From the results of the analysis it can be concluded that: 1) Service quality consisting of speed, friendliness, knowledge, number of services and appearance of formality simultaneously has a significant effect on public satisfaction in customer service of sharia business units. 2) Service quality consisting of speed, friendliness, knowledge, number of services and appearance of formality has a partial significant effect on public satisfaction in customer service of sharia business units 3) Display of formality has a dominant effect on public satisfaction in customer service for sharia business units (Y).